Conflict in decision making and variation in public administration outcomes in Italy during the COVID‐19 crisis - Malandrino, Anna (Eur Policy Anal, 2020)
Italy has been heavily affected by the COVID‐19 pandemic. National and subnational authorities have introduced several measures to tackle the resulting crisis, including social distancing and restrictions on economic activities. However, as we will show in this contribution, such measures have sometimes resulted in uncertainty concerning the allocation of decision making powers along the central–local government continuum and regarding the exercise of administrative tasks by public authorities, thus producing conflict and variation within the policymaking and policy‐delivery processes in Italy. To show this, we review the relevant events that occurred during the pandemic in the country in light both of the literature on centralization and discretion and of the principles shaping the Italian legal system. Our analysis, based on a dialogue between political science and public law, allows us to read the Italian case as a mix of inadequate institutional coordination and insufficient and unclear central guidelines which ultimately produced uncertainty, which together had a direct impact on policymakers, policy‐deliverers, and citizens in general.